Angiomatoid fibrous histiocytoma: unusual sites and unusual morphology - Chen, Gang; Folpe, Andrew L; Colby, Thomas V; Sittampalam, Kesavan; Patey, Martine; Chen, Ming-Guang; Chan, John K C (Modern pathology, 2011)
Angiomatoid fibrous histiocytoma is a soft tissue neoplasm of low malignant potential, typically occurring in the superficial soft tissues of the extremities in children and young adults. Occurrence outside somatic soft tissues is most uncommon. This report describes eight such cases, involving the lung (three cases), mediastinum (one case), vulva (two cases), retroperitoneum (one case) and ovary (one case), with the latter three locations being hitherto unreported sites of occurrence. Patients had a median age of 48 years, and presented with symptoms related to the mass lesion (five cases) or were incidentally found to harbor a tumor (three cases). Besides the typical histological features such as an outer shell of lymphoid tissue, multinodular aggregates of dendritic-like tumor cells, blood-filled spaces and abundant admixed plasma cells, unusual features were found focally in some cases, including clear cells, rhabdomyoblast-like cells, pulmonary edema-like pattern and tumor cell cords lying in a myxoid stroma. Immunoreactivity for the epithelial membrane antigen, desmin, smooth-muscle actin, CD68 and CD99 was found in 100, 63, 43, 100 and 100% of cases, respectively. Molecular studies provided support for the diagnosis in all seven tested cases—EWS gene translocation in six cases (partner gene being CREB1 in three and ATF1 in two in which information was available) and FUS gene translocation in one case. Comparison of the reported cases of extrasomatic angiomatoid fibrous histiocytoma with their somatic soft tissue counterparts showed a number of differences: higher mean age, slight male predominance (particularly for bone lesions), larger tumors, higher frequency of systemic symptoms, higher recurrence rate, myxoid change being more common and a much higher frequency of EWS/ATF1 gene fusion.